1994
DOI: 10.1002/jez.1402700304
|View full text |Cite
|
Sign up to set email alerts
|

Brief treatment with an aromatase inhibitor during sex differentiation causes chromosomally female salmon to develop as normal, functional males

Abstract: Although many studies implicate sex steroids in the process of sexual differentiation, the exact role played by these substances in lower vertebrates, especially teleost fish, is not clear, since it is not conclusively known whether sex steroids are the cause or an early consequence of sex differentiation. By hormonal manipulation and specific crossings, it is possible to produce allfemale stocks of the otherwise gonochoristic chinook salmon (Oncorhynchus tshawytscha). These allfemale stocks are an excellent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
113
1
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(131 citation statements)
references
References 22 publications
8
113
1
3
Order By: Relevance
“…In addition, Fadrozole has previously been shown to induce male development by blocking the aromatization of androgens to estrogens in many taxa (Piferrer et al, 1994;Wibbels and Crews, 1994;Chardard and Dournon, 1999;Warner et al, 2005). Intriguingly, our results in two turtle species across four independent experiments are inconsistent with 13 these well-established findings; the application of Fadrozole had no impact on offspring sex ratios in the present study, and applying estradiol to eggs produced nearly all male offspring, a pattern opposite of expectations.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In addition, Fadrozole has previously been shown to induce male development by blocking the aromatization of androgens to estrogens in many taxa (Piferrer et al, 1994;Wibbels and Crews, 1994;Chardard and Dournon, 1999;Warner et al, 2005). Intriguingly, our results in two turtle species across four independent experiments are inconsistent with 13 these well-established findings; the application of Fadrozole had no impact on offspring sex ratios in the present study, and applying estradiol to eggs produced nearly all male offspring, a pattern opposite of expectations.…”
Section: Discussioncontrasting
confidence: 99%
“…The lack of an effect of Fadrozole on offspring sex ratios is difficult to explain considering the wealth of studies that demonstrate its masculinizing effect on gonads (e.g., Piferrer et al, 1994;Wibbels and Crews, 1994). In the case of one previous study using Fadrozole with the turtle Trachemys scripta, a near pivotal incubation temperature was used in an attempt to increase the sensitivity of the embryos to Fadrozole , so it is possible that the higher incubation temperature (30°C) used in the current study obscured the effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing evidence in fish that multiple loci exist encoding at least two distinct isozymes of CYP19 that are differentially expressed in the brain and ovary (Kuhl et al, 2005). The potential for aromatase inhibitors to adversely affect sexual differentiation and reproduction in fish was demonstrated in an early study by Piferrer et al (1994), and similar results have been reported by Afonso et al (1999Afonso et al ( , 2000, Kitano et al (2000), Ankley et al (2002), andPanter et al (2002).…”
Section: Introductionmentioning
confidence: 59%
“…Sex inversions in fish exposed to EDCs have been reported previously (Yamamoto, 1953;Edmunds et al, 2000;Iwamatsu et al, 2000;Kitano et al, 2000) and may involve androgenic chemicals eliciting male characteristics in -Mercier et al, 1995;Belaid et al, 2001), red spotted grouper (Epinephelus akaara) (Li et al, 2005), chinook salmon (Oncorhynchus tshawytscha) (Piferrer et al, 1994), Japanese flounder (Paralichthys olivaceus) (Kitano et al, 2000) and zebrafish (Danio rerio) (McAllister and Kime, 2003;Andersen et al, 2004;Fenske and Segner, 2004) with different life stages exposed to AIs. However, some uncertainties remain.…”
Section: Discussionmentioning
confidence: 86%